2010
DOI: 10.1093/ejechocard/jep207
|View full text |Cite
|
Sign up to set email alerts
|

Combining blood flow and tissue Doppler imaging with N-terminal pro-type B natriuretic peptide for risk stratification of clinically stable patients with systolic heart failure

Abstract: AimsThis study was designed to ascertain whether the combination of Doppler assessment of the ratio of mitral blood flow to myocardial early diastolic velocities (E/E m ratio) and plasma N-terminal pro-type B natriuretic peptide (NT-proBNP) testing is useful to better stratify patients with stable systolic heart failure (HF). Methods and resultsA total of 362 outpatients with chronic systolic HF (left ventricular ejection fraction 45%) underwent clinical assessment, NT-proBNP testing, and comprehensive echo-Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This suggests that diastolic stretch is one of the major determinants of NP induction [34]. Finally, in a more recent study that compared BNP levels with venous pressure, capillary wedge pressure, and diastolic filling pattern, evaluated by echo, authors showed that as BNP cutoff >400 pg/mL is able to identify patients with higher wedge pressure, it correlates well with all hemodynamic parameters [35]. …”
Section: The Current and Potential Role Of Np In Heart Failurementioning
confidence: 99%
“…This suggests that diastolic stretch is one of the major determinants of NP induction [34]. Finally, in a more recent study that compared BNP levels with venous pressure, capillary wedge pressure, and diastolic filling pattern, evaluated by echo, authors showed that as BNP cutoff >400 pg/mL is able to identify patients with higher wedge pressure, it correlates well with all hemodynamic parameters [35]. …”
Section: The Current and Potential Role Of Np In Heart Failurementioning
confidence: 99%
“…We need a better way to titrate and personalize therapy in our HF patient (Table  2). It is up to the cardiology and echocardiography community to build the missing evidence required to shift the practice of HF from art of clinicians to evidence- based tailored and individualized treatment of HF guided by low cost portable radiation-free imaging techniques [39,40]. …”
Section: Resultsmentioning
confidence: 99%
“…The value of integrated NPs and echo‐guided management of outpatients with chronic HF can be established when this strategy will be prospectively compared with the standard of care . In a recent retrospective study, we observed a greater survival benefit in patients in the echo‐ and BNP‐guided group than in a clinically guided group (Figure ).…”
Section: Combining Echo and Natriuretic Peptides During Follow‐upmentioning
confidence: 85%